Enhanced collaborative E-learning for programming using open learner model / Mahfudzah Othman, Siti Hana Quzaima Alias and Nur Fajrina Mohd Rashidi - Othman, Mahfudzah; Alias, Siti Hana Quzaima; Mohd Rashidi, Nur Fajrina (UiTM Cawangan Perlis, 2016)
Open learner model is mainly used to depict learner’s achievements and progress in particular subject using variety of qualitative representations ranging from simple representations such as skill meters to more complex Bayesian network models. Currently, open learner models are only available for individual learners and mostly used separately from e-Learning systems. Therefore, this paper proposed an enhanced model of collaborative e-learning by integrating open learner model that will represent students’ achievements and milestones while learning introductory programming course. The aim is to produce learner models using graphical skill meters that are not only used to reflect individual performances, but also a group of learners’ academic achievements and milestones. Through this, learners will be able to reflect their own performances in introductory programming subject and become more engaged and responsible towards their own progress.